The Harvard medical school guide to tai chi : 12 weeks to a healthy body, strong heart, and sharp mind - Wayne, Peter M. (Shambhala, 2013)
Conventional medical science on the Chinese art of Tai Chi now shows what Tai Chi masters have known for centuries: regular practice leads to more vigor and flexibility, better balance and mobility, and a sense of well-being. Cutting-edge research from Harvard Medical School also supports the long-standing claims that Tai Chi also has a beneficial impact on the health of the heart, bones, nerves and muscles, immune system, and the mind. This research provides fascinating insight into the underlying physiological mechanisms that explain how Tai Chi actually works.